Genomic research, publics and experts in Latin America: Nation, race and body. (December 2015) - Wade, Peter; López-Beltrán, Carlos; Restrepo, Eduardo; Santos, Ricardo Ventura
The articles in this issue highlight contributions that studies of Latin America can make to wider debates about the effects of genomic science on public ideas about race and nation. We argue that current ideas about the power of genomics to transfigure and transform existing ways of thinking about human diversity are often overstated. If a range of social contexts are examined, the effects are uneven. Our data show that genomic knowledge can unsettle and reinforce ideas of nation and race; it can be both banal and highly politicized. In this introduction, we outline concepts of genetic knowledge in society; theories of genetics, nation and race; approaches to public understandings of science; and the Latin American contexts of transnational ideas of nation and race.